Fibronectin in hyperglycaemia and its potential use in the treatment of diabetic foot ulcers: A review - Kanta, Jiri; Zavadakova, Anna; Sticova, Eva; Dubsky, Michal (International wound journal, 2023)
Metabolism of fibronectin, the protein that plays a key role in the healing of wounds, is changed in the patients with diabetes mellitus. Fibronectin can interact with other proteins and proteoglycans and organise them to form the extracellular matrix, the basis of the granulation tissue in healing wounds. However, diabetic foot ulcers (DFUs) suffer from inadequate deposition of this protein. Degradation prevails over fibronectin synthesis in the proteolytic inflammatory environment in the ulcers. Because of the lack of fibronectin in the wound bed, the assembly of the extracellular matrix and the deposition of the granulation tissue cannot be started. A number of methods have been designed that prevents fibronectin degradation, replace lacking fibronectin or support its formation in non-healing wounds in animal models of diabetes. The aim of this article is to review the metabolism of fibronectin in DFUs and to emphasise that it would be useful to pay more attention to fibronectin matrix assembly in the ulcers when laboratory methods are translated to clinical practice.
Keywords: Extracellular Matrix; extracelulární matrix; Hyperglycemia; zvířata; hyperglykemie; diabetická noha; diabetes mellitus; Diabetes Mellitus; Fibronectins; Wound Healing; Animals; fibronektiny; hojení ran; Diabetic Foot